State and laid-off workers in reform China : the silence and collective action of the retrenched - Cai, Yongshun (Routledge studies--China in transition, 2006)
In the 1990s, the Chinese government launched an unprecedented reform of state enterprises, putting tens of millions of people out of work. This empirically rich study calls on comprehensive surveys and interviews, combining quantitative data with qualitative in its examination of the variation in workers' collective action. Cai investigates the difference in interests of and options available to workers that reduce their solidarity, as well as the obstacles that prevent their coordination. In addition, and perhaps more importantly, this book explores the Chinese Government's policies and h.